Investigation of the Impact of Aging Upon the Mechanical Properties of Cocoa Pod Husk - Renique Murray; Sanjay Bachu; Cilla Pemberton; Robert Birch (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
The husk of fresh cocoa pods has traditionally been considered a waste by-product in the production of chocolate and other related confectionaries. However, in recent times new research has shed light on an increasing number of uses for this material. Of particular interest are applications that utilize the cocoa pod husk (CPH) for its mechanical properties. In most instances, the CPH raw material is allowed to age for several days before pre-processing or utilization in the intended application. Despite this, the impact of aging on its mechanical properties is an area that has not been well investigated. Consequently, this work seeksto determine the impact of aging upon the mechanical properties of CPH. To investigate this, several CPH properties were identified and selected for evaluation. These included CPH tensile strength, CPH compressive strength, cocoa pod transverse compressive strength, cocoa pod longitudinal compressive strength, CPH cutting force, cocoa pod cutting force, CPH hardness, and CPH colour. These properties were subsequently assessed over an aging period of seven days. The results obtained indicated that most CPH mechanical properties vary significantly with aging time. Moreover, CPH colour was found to bestrongly related to the mechanical properties of pod longitudinal compressive strength and CPH hardness, with correlation coefficients of -0.71 and 0.86 respectively. Further, these relationships were found to be strongly linear in nature and regression analyses indicated that up to 83% of the variation in longitudinal compressive strength can be accounted for by changes in colour, hardness and aging time. These results provide the basis for the potential development of image analysis and computer vision approaches to CPH sorting and grading.